Pengembangan Aplikasi Mobile Pembelian Tiket Pariwisata Di Kabupaten Wonogiri (Kasus Waduk Gajah Mungkur) - Rusli Pramono; Anita Fira Waluyo (LPPM STIKOM Tunas Bangsa, 2023)
The tourism sector is one of the sectors that can support the economy of a region. A region can utilize its geographical conditions to be used as tourist attractions. Continuous innovation has led to advancements in the tourism sector. Currently, there are many new tourist destinations, both natural and man-made. However, challenges have arisen due to the proliferation of tourist destinations, leading to increased competition among them, with many places becoming less crowded and even unknown to the public. One of the contributing factors to this issue is the lack of effective promotion of these tourist destinations.The development of an application is carried out on mobile devices, especially smartphones with the Android operating system. This application development also employs a framework to ensure the security of the web admin. The framework used for this purpose is the Laravel framework.The development of an e-ticketing application for the Waduk Gajah Mungkur tourist destination is an effort to keep up with the times. The e-ticketing application aims to digitalize the ticket purchasing process to make it more effective and efficient.